Evaluación de niveles de radiación no ionizante producidas por las líneas de transmisión de 230 kV en la zona de Quevedo - Casanova Párraga, Roy Alfredo (2012)
This research was conducted in the canton Quevedo, Los Rios Province, the main purpose of it was to measure levels of non-ionizing radiation produced by the transmission lines (high voltage), and the main objective was: To evaluate the radiation levels non-ionizing radiation produced by electrical transmission lines of 230 kV in the area of Quevedo, and specific objectives were met: Monitor the amount of electromagnetic radiation produced by electrical transmission lines in the section Quevedo - Four sleeves; determine the effects caused by electromagnetic fields in people exposed to such radiation, Get a thematic map with the monitoring results and, Develop a proposal for environmental education to help decrease the effects of such radiation, if any. The hypothesis was: The levels of non-ionizing radiation produced by electrical transmission lines do not exceed the proposed standard by the International Commission for Protection on Non-Ionizing Radiation Protection (ICNIRP). For the fieldwork (data collection), we used a Lutron EMF radiation meter 839 and was used Likert questionnaire to evaluate the criterion of the population (public perception), the effects caused by transmission lines (high voltage) in the population exposed to them. The tabulation of results was done based on the experimental design completely randomized blocks (ANOVA 2), and comparison of results was performed using the ICNIRP regulations and Unified Text of Secondary Legislation Ministry of Environment (TULSMA). Thematic mapping was performed using the software Arc GIS 9.3, obtaining maps of the electric field, magnetic field and magnetic flux density. According to the results obtained compared with the current regulations are not recorded effects on the health of people exposed, however if one takes into account the public perception, if any encumbrances less than the health of the population, thus accepts the hypothesis "The level of non-ionizing radiation produced by electrical transmission lines do not exceed the proposed standard by the International Commission for Protection on Non-Ionizing Radiation Protection (ICNIRP)" It is concluded that property owners do not respect rural and urban fringe width easement (30 meters to the sides of the transmission line), the banana plantations that are under the transmission line as the Hacienda El Porvenir, states both crops and farm workers to electromagnetic radiation.